Cost-effectiveness of selective caries removal versus stepwise excavation for deep caries lesions - Juliana Jobim Jardim; Luana Severo Alves; Roberto Frota Decourt; Lilian Marly de Paula; Heliana Dantas Mestrinho; Marisa Maltz (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract A multicenter, randomized controlled clinical trial evaluated the effectiveness of two treatments for deep caries lesions in permanent molars - selective caries removal (SCR) to soft dentin with restoration in a single visit, and stepwise excavation (SW) - regarding pulp vitality for a 5-year follow-up period. The present study aimed to determine the cost-effectiveness of these treatments. Treatments were conducted in two Brazilian cities (Brasília and Porto Alegre). At baseline, 299 permanent molars (233 patients) were treated and 229 teeth (174 patients) were evaluated after 5 years. The discounted cash flow method was adopted. The total cost of each treatment was calculated, and the failure cost (endodontic treatment + restoration) was added to the final cost, according to the 5-year failure rates of each therapy (20% for SCR and 44% for SW). A public health service unit composed of three dentists in 4-hour work shifts was used to calculate the monetary value of the treatments, assuming a total of 528 treatments/month. Considering the 229 teeth evaluated after 5 years (115 SCR and 114 SW), SCR provided savings of 43% (amalgam) and 41% (resin composite) per treatment, compared to SW. The SCR technique provides benefits for public finances (direct economy) and for public health services (increase in the number of treatments performed). Considering that maximizing profit and reducing costs are powerful motivating factors for adopting a certain treatment, this study provides data to better support the decision-making process, regarding the management of deep caries lesions in permanent molars.